The Correlation Between Students' Learning Technique and Students' Mathematics Achievement - Sigamura, Radha Krisnamurti; Herawati (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study addresses a critical gap in STEM education literature by empirically investigating the underexplored relationship between structured learning techniques and mathematics achievement in Indonesian engineering education—a context with limited prior research despite documented pedagogical challenges. Using a quantitative correlational design, we examined 100 engineering students at Musi Rawas University through triangulated data collection: structured interviews (14-item protocol), observational checklists (10-point behavioral scale), and institutional academic records. Participants were purposively sampled and categorized into structured (n=68) and unstructured (n=32) learners based on a validated 10-point analytical rubric (inter-rater reliability κ=0.87). Data analysis employed Pearson correlation, t-tests, and regression modeling. Findings revealed a robust positive correlation between structured techniques (concept mapping, scheduled reviews) and mathematics achievement (r = .79, p < .001), accounting for 62.4% of variance (R² = .624). Structured learners significantly outperformed peers (84.1 vs. 61.5; t(98) = 12.6, p < .001), with concept mapping identified as the highest-impact strategy (β = .42). Notably, cramming demonstrated significant negative correlations (r = −.67, p < .01). These results substantiate cognitive load theory while highlighting the 32% prevalence of ineffective techniques—a key pedagogical concern. The study implies that embedding structured strategy training (e.g., concept mapping scaffolding) into engineering curricula could elevate mathematics performance by 20–30%. Limitations include single-institution sampling and self-reporting biases, warranting future multi-institutional validation. This research provides actionable evidence for optimizing STEM learning processes in Indonesian contexts